Effective mydriasis in juvenile loggerhead turtles (Caretta caretta) following topical administration of rocuronium bromide and 10% phenylephrine. (23rd May 2019) - Petritz, Olivia A.; Westermeyer, Hans D.; Whitehead, Michelle C.; Christiansen, Emily F.; Lohmann, Kenneth J.; Lohmann, Catherine M. F.; Lewbart, Gregory A.
Abstract: Objective: To determine the combined mydriatic effects of topical rocuronium bromide and phenylephrine in juvenile loggerhead turtles and identify any adverse effects associated with treatment. Animals studied: Eleven juvenile loggerhead turtles ( Caretta caretta ). Procedures: Four 20 μL drops of rocuronium bromide and four 20 μL drops of 10% phenylephrine were placed into the right eye at 2‐minute intervals of 5 turtles, while the same volume of saline was administered to six control turtles. A pupilometer recorded pupil measurements at rest and following a light stimulus at 2, 15, 30, 60, 120, 150, 180, 210, 240, 300, and 360 minutes following delivery of the final drop to the ocular surface. Intraocular pressure (IOP) was also measured at similar time points. Results: The nonilluminated and light‐stimulated pupillary diameter of the right eye of treated turtles was significantly greater than baseline starting at 120 and 15 minutes, respectively. Light‐stimulated pupillary diameter of treated eyes was greater than that of control eyes from time 15 minutes until the end of the treatment period. No systemic side effects were noted over a 24 hours period following treatment and all turtles showed normal behavior and appetite. No mydriasis was noted in either eye at 24 hours and the anterior segment was normal. Conclusions: A combination of topical ophthalmic rocuronium bromide and 10% phenylephrine is safe and effective for mydriasis in juvenile loggerhead turtles.